Effect of driving pressure-guided positive end-expiratory pressure on respiratory mechanics and clinical outcomes in surgical patients: a systematic review and meta-analysis of randomized controlled trials - Yu-han Sun; Xing-long Yang; Bin-bin Dong; Qi Liu (Annals of Medicine)
Background Intraoperative driving pressure-guided positive end-expiratory pressure (PEEPdp) is effective for reducing postoperative pulmonary complications (PPCs). However, its impact on respiratory mechanics and clinical outcomes requires further elaboration.Methods PubMed, the Cochrane Library, Web of Science and Embase were searched from inception to May 2024 for randomized controlled trials (RCTs) comparing the effect of PEEPdp with conventional fixed positive end-expiratory pressure (PEEP) in patients undergoing surgery. The primary outcomes were the effects on the driving pressure (DP), static respiratory compliance and plateau pressure (Pplat). Secondary outcomes included the effects on common clinical outcomes and the incidence of PPCs. Risk ratios or mean differences were pooled using fixed- or random-effects models.Results Nineteen RCTs involving 3744 patients were included. The mean of PEEPdp was 8.2 cmH2O with 95% CI from 7 cmH2O to 9.5 cmH2O, while the median of PEEP in the conventional group was 5 cmH2O with an interquartile range of 1 cmH2O. Patients in the PEEPdp group were ventilated with lower DP (mean: 10 cmH2O, 95% CI [8.8, 11.1] vs. mean: 11.9 cmH2O, 95% CI [10.6, 13.3]; p < .00001), and increased respiratory compliance (mean: 46.4 ml/cmH2O, 95% CI [42.1, 50.7] vs. mean: 39 ml/cmH2O, 95% CI [35.2, 42.8]; p < .0001) with nonsignificant Pplat. PEEPdp did not significantly affect intensive care unit (ICU) admission, mortality or length of hospital and ICU stay (p > .05), but it reduced the incidence of PPCs (p = .001). The benefits were especially evident in patients undergoing abdominal surgery, those with DP less than 10 cmH2O or those with PEEPdp ranging from 5 to 10 cmH2O or when PEEPdp was titrated via a stepwise increase method (p < .05).Conclusions PEEPdp allows for ventilation with lower DP, improved static respiratory compliance and fewer PPCs. No significant effects were observed on broader clinical outcomes per current data.